A call to leverage a health equity lens to accelerate human neuroscience research - Rebello, Vida; Uban, Kristina A. (Frontiers in Integrative Neuroscience, 2023)
Investigation of health inequities tends to be examined, in human neurosciences, as biological factors at the level of the individual. In actuality, health inequities arise, due largely in part, to deep-seated structural factors. Structural inequality refers to the systemic disadvantage of one social group compared to others with whom they coexist. It encompasses policy, law, governance, and culture and relates to race, ethnicity, gender or gender identity, class, and sexual orientation. These factors include social segregation, the intergenerational effects of colonialism, and the distribution of power and privilege. Principles to address inequities influenced by structural factors are increasingly prevalent in a subfield of neurosciences i.e., cultural neurosciences. Cultural neuroscience articulates the bidirectional relationship between biology and environmental factors surrounding research participants. However, the operationalization of these principles may not have the spillover effect on the majority of human neurosciences: this limitation is the overarching focus of the present perspective. Here, we provide our perspective that these principles are missing and needed in all human neuroscience subdisciplines to accelerate our understanding of the human brain. Furthermore, we provide an outline of two tenets of a health equity lens for achieving equity in human neurosciences: the social determinants of health (SDoH) framework and how to deal with confounders using counterfactual thinking. We argue that these tenets should be prioritized across general human neuroscience research to further gain an understanding of contextual background intertwined with the human brain, thus improving the rigor and inclusivity of human neuroscience research.